2022
DOI: 10.3390/vetsci9030130
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nosema ceranae (Microsporidia: Nosematidae) in Honey Bee Colony Losses and Current Insights on Treatment

Abstract: Honeybee populations have locally and temporally declined in the last few years because of both biotic and abiotic factors. Among the latter, one of the most important reasons is infection by the microsporidia Nosema ceranae, which is the etiological agent of type C nosemosis. This species was first described in Asian honeybees (Apis cerana). Nowadays, domestic honeybees (Apis mellifera) worldwide are also becoming infected due to globalization. Type C nosemosis can be asymptomatic or can cause important damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 122 publications
(184 reference statements)
0
14
0
4
Order By: Relevance
“…If this was the case, it is possible that N. ceranae spores hitchhiked along with V. destructor in the queens parcels illegally imported in 2000, as this pathogen has been shown to be infecting A. mellifera since at least 1995 in the USA [ 17 ] and 1998 in Europe [ 69 ]. Alternatively, Pico did not act as the entry point in the Azores and N. ceranae could have been introduced later to this island through contaminated hive products [ 70 , 71 , 72 ], originating from the varroa-free islands, mainland or elsewhere, and V. destructor aided infection development by lowering the immune defences of the honey bees [ 73 , 74 , 75 ]. If the first hypothesis is true, then the stringent restrictions on the circulation of honey bees and hive products from the varroa-invaded islands onto the varroa-free islands, imposed early by the veterinary authority (Dr. Paula Vieira, pers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this was the case, it is possible that N. ceranae spores hitchhiked along with V. destructor in the queens parcels illegally imported in 2000, as this pathogen has been shown to be infecting A. mellifera since at least 1995 in the USA [ 17 ] and 1998 in Europe [ 69 ]. Alternatively, Pico did not act as the entry point in the Azores and N. ceranae could have been introduced later to this island through contaminated hive products [ 70 , 71 , 72 ], originating from the varroa-free islands, mainland or elsewhere, and V. destructor aided infection development by lowering the immune defences of the honey bees [ 73 , 74 , 75 ]. If the first hypothesis is true, then the stringent restrictions on the circulation of honey bees and hive products from the varroa-invaded islands onto the varroa-free islands, imposed early by the veterinary authority (Dr. Paula Vieira, pers.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of N. ceranae on the varroa-free islands likely occurred via commercial hive products, as the importation of queens or packaged honey bees has been restricted for over 22 years. Honey, pollen, royal jelly, and wax foundation can all contain viable spores and thus operate as transmission vehicles of N. ceranae through trading [ 70 , 71 , 72 ]. Among these, the wax foundation is the more probable original source of introduction in the varroa-free islands because there is a high demand for this hive product in the Azores and sterilisation of wax imports has only been compulsory since 2010 (Dr. Paula Vieira, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Ariana and his colleagues concluded that a spray of 2% thyme, spearmint, and savory essential oil has no harmful effect on honey bees compared to dillsun essence, which caused 12% honey bee mortality [ 12 ]. Another study estimated that an essential oil of Citrus paradisi and C. sinensis reduced Paenibacillus, and at the tested concentrations of 2.34 mg/L, 2.08 mg/L, 1.82 mg/L, 1.56 mg/L, and 1.30 mg/L, had no mortality of honey bees [ 15 ]. Screening the toxicity activity of 13 crude plant extracts, Piper ribesioides and P. sarmentosum were found to be highly toxic to bees but Thunbergia laurifolia , Allium sativum , Cymbopogon citratus , and Senna alata had no toxic effect on adult bees, even those exposed to a high concentration [ 16 ].…”
Section: Safety Of Natural Products As Treatments Of Nosemosismentioning
confidence: 99%
“…These factors are (i) queen bees’ genetic origins and hygienic behavior; (ii) pathogenic agents, such as parasites, bacteria, viruses, fungi, and protozoa, which differ in their degrees of presence, virulence, and infectious load; and (iii) environmental conditions, including humidity, temperature, and presence of nectar plants, as nectar secondary metabolites reduce the likelihood of parasitic infection, in addition to bad beekeeping practices [ 13 , 14 ]. Many biological pathogens are responsible for bee colony mortality, including parasites such as nosema [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the article reports the efficacy of plant extracts, nutraceuticals, probiotics, propolis, and veterinary drugs as alternative treatment strategies. They might be a substitute for the commonly used antibiotic fumagillin, which is prohibited in the European Union [ 14 ].…”
mentioning
confidence: 99%